Awareness of the benefits of sign bilingual education in the education of deaf children in Zimbabwe - Sibanda, Patrick (Pure and Applied Science Advances, 2018)
The study sought to interrogate the extent administrators, teachers and deaf children in the few mainstream schools that used sign bilingual education in Zimbabwe were aware of the benefits of sign bilingual education. The study adopted the mixed methods approach which is grounded in the philosophy of pragmatism. Employing the sequential explanatory design, the study involved 100 teachers, 30 administrators and 30 deaf children from schools that used sign bilingual education from the Bulawayo Metropolitan Province for the quantitative phase. One administrator and 6 teachers per school were engaged in the qualitative phase. Questionnaires were used to collect quantitative data while personal face-to-face and focus group interviews (FGIs) were used to collect qualitative data. The integrated results of the study indicated evidence of awareness of the benefits of sign bilingual education in the education of deaf children in inclusive mainstream schools in Zimbabwe. From the results, the study concluded that such awareness implied potential for more effective practice of sign bilingual education in the country in order to advance these benefits. Ultimately, the study recommended further research and proposed a framework of practice termed ‘Sibanda’s Framework of the Practice of Sign Bilingual Education in Zimbabwe.